KEANEKARAGAMAN JENIS TUMBUHAN PTERIDOPHYTA DI HUTAN KAKAHA DESA PRAIWITU KABUPATEN SUMBA TIMUR SEBAGAI SUMBER BELAJAR BIOLOGI - Kambombu, Simson Hiwal; Ina, Anita Tamu (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
Research to describe the prevalence of Pteridophyta species in the Kakaha Forest of Praiwitu Village, East Sumba, and to explain how Pteridophyta species are used as subjects of biological instruction in the form of textbooks. The data collection technique was carried out using a purposive sampling method, namely by making transect lines in several locations representing Ptedirophyta plants in the Kakaha Forest, Praiwitu Village. Data from this study will be analyzed descriptively, and samples will be identified based on morphological characteristics to match their characteristics with an index to help their knowledge of diversity. Based on the results of the data analysis and discussion that has been described, it can be concluded as follows: The results of the identification of ferns found in the Kakaha Forest are 17 species of ferns consisting of 4 classes, namely class filicinae 4 Order, flicopsida 1 Order, pteridopsida 3 Order, and lycopodiopsida class 1 Order, 9 families, and 13 genera. The results of the calculation of Pteridophyta plants in the Kakaha Forest from the observation of the ecological index are the value of the density totaling 127.4 individuals, the relative density is 1000 individuals, the dominance index is 0.068371 individuals in the low category, and the diversity index value is 3.279 individuals in the medium category.